Movimento antifeminista: discursos e ativismos de mulheres nas redes sociais, impressos e eventos (2015 – 2019) - Oliveira, Carem Aline de (2020)
This dissertation starts from the problematization of anti-feminist discourses produced by women who disqualify feminism via social networks, building the feminist subject through the production of discourses that evoke debates about social values, gender and the roles intrinsic to it. At the same time, we also characterize anti-feminism as a social movement, we define the theoretical and political bases that constitute and drive its discourse and the movement's agenda, the connections of anti-feminist speeches with those propagated by other conservative sectors and their relationship with state proposals that cause setbacks in debates about rights for women and minorities. For that, we analyzed a set of social media posts that are called anti-feminists, in addition to antifeminist content produced outside the internet, between the years 2015 to 2019. The theoretical methodological framework of the analyzes, are based on the theoretical assumptions of Michel Foucault about of the discourse, of the subject, of the knowledge and powers and of the Gender Studies that allow us to problematize the organization and the discursive construction of the gender through the transmission of social performances, selected and organized according to their social value and their correspondence to these values, for the maintenance and fixation of femininity “ideas” that govern the antifeminist discourse.